Motivation in learning English: A Case Study of Second-Year Students at Saigon university - Thuy Phuong Nguyen; Nhu Ngoc Huynh (English Education and Applied Linguistics Journal (EEAL Journal), 2025)
This study investigated motivation in language learning through a questionnaire distributed to 108 second-year students at the Faculty of Foreign Languages, Saigon University. The findings reveal that the students demonstrate a relatively positive attitude toward learning English. In the relationship between academic performance and learning motivation, the motivation to learn English for better job opportunities ranks highest (accounting for 73.1%), as students believe it is essential for achieving material success after graduation. The motivation to gain promotion opportunities in the future also holds a relatively high percentage (67.6%), followed by the motivation to learn English for entertainment purposes (66.7%), the belief that English is a global language (64.8%), and the desire to communicate with foreigners (61.1%). In addition, the motivation to learn English for travel purposes also shows a fairly high proportion (58.3%). These factors all have an impact on students’ academic performance. The findings of the study offer useful suggestions for both students and lecturers in overcoming challenges in teaching and learning, helping students develop a more active and positive learning motivation.